2020
DOI: 10.1002/ejoc.202001300
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (E)‐3‐Alkylideneindolin‐2‐ones by an Iron‐Catalyzed Aerobic Oxidative Condensation of Csp3–H Bonds of Oxindoles and Benzylamines

Abstract: A novel synthetic route for the construction of (E)‐3‐alkylideneindolin‐2‐ones through iron‐catalyzed aerobic oxidative condensation of oxindoles with benzylamines has been developed. This oxidative reaction involves a sequence of C–H activation, amine self‐condensation, nucleophilic addition, and C–C double bond formation. The synthetic importance of this protocol has been demonstrated by preparing tyrosine kinase inhibitors, anticonvulsant and antitumor agents, and other valuable 3‐alkylideneindolin‐2‐one de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The use of a biocatalyst such as porcine pancreas lipase (PPL) in the Knoevenagel condensation of oxindole and various aromatic aldehydes allows one to perform the reaction with high selectivity towards the E configuration [32]. Also, iron-catalyzed aerobic oxidative condensation of oxindoles with benzylamines was reported to result in selective formation of (E)-3-alkylideneindolin-2-ones [33], although this is not a Knoevenagel condensation. Contrariwise, the Ti(OiPr) 4 /pyridine system, which was first proposed by Robichaud and Liu [34] to provide Knoevenagel olefin products, was further used for selective synthesis of (Z)-3-alkylideneoxindoles from unsymmetrical ketones, but not aldehydes [35].…”
Section: Resultsmentioning
confidence: 99%
“…The use of a biocatalyst such as porcine pancreas lipase (PPL) in the Knoevenagel condensation of oxindole and various aromatic aldehydes allows one to perform the reaction with high selectivity towards the E configuration [32]. Also, iron-catalyzed aerobic oxidative condensation of oxindoles with benzylamines was reported to result in selective formation of (E)-3-alkylideneindolin-2-ones [33], although this is not a Knoevenagel condensation. Contrariwise, the Ti(OiPr) 4 /pyridine system, which was first proposed by Robichaud and Liu [34] to provide Knoevenagel olefin products, was further used for selective synthesis of (Z)-3-alkylideneoxindoles from unsymmetrical ketones, but not aldehydes [35].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the utility of this methodology was applied to the synthesis of 9-amino-6-chloro-2-methoxy acridine (ACMA, Scheme 1), which is an important scaffold in drug compounds such as mepacrine (antimalarial) and quinpramine (antiprion). [43][44] Besides, many of the synthesized 9-aminoacridine compounds, viz., 2-methoxy-9-acridinamine (4a), 3-methyl-9-acridinamine (5b) and 4-methyl-9-acridinamine (5e) are used as precursors for the synthesis of bioactive molecules. [45][46][47] To test the feasibility of the Buchwald-Hartwig amination for different halogen partners, we performed the reactions with 2-chlorobenzonitrile, 2-iodobenzonitrile, and 2-iodo-4-methylbenzonitrile under the optimized catalytic conditions (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Gnanaprakasam's group reported that Ru(II)-NHC promoted the synthesis of 3-(diphenylmethylene)indolin-2-one by using diaryl methanols and 2-oxindole as substrates [25]. Gopalaiah and coworkers finished iron-catalyzed direct access to (E)-3-alkylideneindolin-2-ones with oxindoles and benzylamines [26]. As we all know, the direct synthesis of 3-alkylideneoxindole was always involved in the oxindoles, which were synthesized by regioselective oxidation of indoles.…”
Section: Introductionmentioning
confidence: 99%